Sikap Pemilih Terhadap Sumber Informasi Hoaks pada Pilpres 2019 di Sumatra Barat - Mohammad Isa Gautama (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
Presidential election in Indonesia has just ended in 2019. As part of the democratic process, elections are expected to be a golden opportunity for all elements to play an active role, especially as voters. In terms of political communication, it is important and interesting to examine the attitude of voters when accepting media exposure about candidates. The urgency is even more crucial based on facts whereas more than 90% of media were fake media. Among 34 provinces in Indonesia, West Sumatra is known as one of the provinces known to be rational. It is interesting to uncover the rationality of the voters in West Sumatra regarding the 2019 Presidential Election. The instrument of study is survey method, questionnaires were distributed to 600 respondents selected based on the stratified random sampling method in 3 cities and 3 districts in West Sumatra. The research finding, 51% of respondents absorb fake media in a raw manner. The result finding is then analysed through a qualitative approach based on relevant references. The conclusion of the study confirms that the majority of the voters of West Sumatra did not use common sense in absorbing information regarding 2019 Presidential election from fake media.